Urgensi Media Komunikasi Internal dan Eksternal Pada Partai Lokal di Aceh Besar - Furqan, Furqan; Hasan, Kamaruddin; Yusnadi, Yusnadi; Samosir, Hasrat Efendi (Jurnal Community, 2024)
This research is aimed at describing how the understanding and application of internal and external media organizational communication ethics of Acehnese local political parties ahead of the 2024 general election. The character, style and pattern of communication within political party organizations have undergone significant changes. This is due to globalization, the information technology revolution has provided hardware or media hardware and software which can be in the form of values, methods, culture adapted by organizational communication actors. So that the members of the organization become more free, democratic and egalitarian. Currently there are almost no political, business and other organizations that can exist without the use of digital media. It is even predicted that in the future it will become more massive and integrative on high-tech or high-tech devices. However, organizational communication through media without being based on ethics can damage all communication arrangements, both internal and external. The method used in this research is a literature study. The results of the study show that the understanding and application of organizational communication ethics through Aceh's local political parties both internally and externally is still weak. So that literacy is needed regarding ethics, organizational communication ethics including media literacy which is one of the supporting tools to help educate the management and members of organizations including the public in political life.